Serum and urine anti-PLA2R antibody correlation with albuminuria in idiopathic membranous nephropathy - Liu, Xiaogang; Fu, Yunfei; Sui, Manshu; Wang, Xuehua; Li, Zizhen (Frontiers in Immunology, 2025)
ObjectiveThis study aimed to investigate the correlation between anti-phospholipase A2 receptor (PLA2R) levels in serum and urine with clinical parameters, particularly albuminuria, in patients with idiopathic membranous nephropathy (IMN).MethodsWe retrospectively analyzed data from 30 patients with biopsy-proven PLA2R-related IMN diagnosed between 2016 and 2022 at two medical centers. Serum and urine anti-PLA2R antibody levels were measured using enzyme-linked immunosorbent assay (ELISA). We assessed the correlation between antibody levels and clinical parameters, including plasma albumin, 24-hour urine protein quantification, and estimated glomerular filtration rate (eGFR). Patients were staged according to the Ehrenreich-Churg classification.ResultsSerum anti-PLA2R antibody levels showed a significant negative correlation with plasma albumin (r = -0.469, P < 0.05), whereas urine anti-PLA2R antibody levels exhibited a weak, but significant, positive correlation with 24-hour urine protein excretion (r = 0.362, P = 0.049). Patients with higher serum anti-PLA2R antibody titers had significantly lower plasma albumin levels (20.63 ± 4.79 g/L) compared to those with lower titers (27.71 ± 6.78 g/L) (P < 0.05). Conversely, patients with higher urine anti-PLA2R antibody titers had significantly higher 24-hour urine protein quantification (9.22 ± 4.17 g) compared to those with lower titers (5.32 ± 3.09 g) (P < 0.05).ConclusionIn patients with IMN, serum anti-PLA2R antibody concentrations are inversely associated with plasma albumin, while urine anti-PLA2R antibody levels are positively associated with 24-hour urine protein quantification. These findings suggest that combined assessment of serum and urine anti-PLA2R antibody levels may provide valuable insights into disease activity and albuminuria in IMN. Further studies with larger cohorts are needed to validate these findings and explore their potential clinical implications.